1993
DOI: 10.1148/radiology.187.3.8388568
|View full text |Cite
|
Sign up to set email alerts
|

Radial scars of the breast: review of 38 consecutive mammographic diagnoses.

Abstract: The authors report 38 consecutive cases of histologically proved breast radial scars (RSs) detected at mammography. In a retrospective review of mammograms in 30 matched cases of nonpalpable RS and nonpalpable scirrhous cancer, the characteristic mammographic features of RS were confirmed: (a) the absence of a central opacity, often substituted by a radiolucent area; (b) the presence of multiple elongated thin spicules radiating from the center of the lesion; (c) the infrequency of any palpable finding, even f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
33
1
6

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 0 publications
6
33
1
6
Order By: Relevance
“…Because of the difficulties assessing these lesions on radiological imaging, the final diagnosis of a radial scar should still be made on histology. 9 The incidence of premalignant or malignant histology in radial scars in this study is comparable with rates reported in the literature. Fasih et al 10 have reported rates from the Newcastle breast screening programme of 67% for pure radial scars, 17% for ADH and 16% for in situ or invasive carcinoma, compared with 68%, 18% and 14% (including LCIS), respectively, in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Because of the difficulties assessing these lesions on radiological imaging, the final diagnosis of a radial scar should still be made on histology. 9 The incidence of premalignant or malignant histology in radial scars in this study is comparable with rates reported in the literature. Fasih et al 10 have reported rates from the Newcastle breast screening programme of 67% for pure radial scars, 17% for ADH and 16% for in situ or invasive carcinoma, compared with 68%, 18% and 14% (including LCIS), respectively, in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Radial scar also has variable associations with the marker lesions for increased breast carcinoma risk, ADH and LCIS. 14,15,18,20,29,30 Most studies have reported an association with ADH, which was seen in 57% of the women in the current study. The incidence of both ADH and LCIS among studies varies, presumably due to population differences, such as symptomatic versus asymptomatic status, patient age, and other risk factors like family or personal history of breast carcinoma.…”
Section: Discussionsupporting
confidence: 51%
“…1,8,12,23 It is widely believed that carcinoma frequently is associated with radial scars and, hence, that patients should be referred for diagnostic excision biopsy rather than needle core biopsy. 12,[15][16][17][18][19] The literature presents a confused picture with regard to the association of carcinoma with radial scar, with the incidence of associated breast carcinoma varying from 0% to 43%. 19,20,22,24,25,29,[31][32][33][34][35] The reported differences in the association of breast carcinoma with radial scars are difficult to reconcile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations